Theoretical analysis and seismic investigation for TBM jamming in squeezing fissile slate. (August 2016) - Koizumi, Yu; Inaba, Takeshi; Yamamoto, Takuji
Abstract: The S tunnel is a 4.2 km-long headrace tunnel. In the tunnelling project, the ground was assumed to be hard slate and suitable for TBM excavation based on the primary site investigation. However, TBM jamming frequently occurred with the increase of the tunnel cover, and the TBM excavation was cancelled. In order to investigate the TBM jamming, theoretical analyses and seismic investigations were conducted. It was found that analytical model proposed in this paper well explained the influence of the cover on the possibility of TBM jamming. It was also found that the depth of the loosened zone was expanded 6–8 m at the location where TBM jamming occurred.